2011
DOI: 10.1111/j.1708-8240.2011.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided‐Design/Computer‐Assisted‐Manufactured Adhesive Restoration of Molars with a Compromised Cusp: Effect of Fiber‐Reinforced Immediate Dentin Sealing and Cusp Overlap on Fatigue Strength

Abstract: Onlays (with or without fibers) increased the fatigue resistance of compromised molars in this in vitro study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
16
1
1
Order By: Relevance
“…Lab composite onlays did not show any significant improvement in the fracture resistance of prepared teeth when compared to lab composite inlays as prepared cusps have less tooth structure, thus could not withstand heavy compressive load . Conversely, this finding did not show any agreement with another previous study which revealed that lab composite onlays (with or without fiber reinforcement) increased the fatigue resistance of restored teeth rather than lab composite inlays as cuspal coverage with lab composite promotes extracoronal strengthening and protects against further crack propagation and fracture tendency.…”
Section: Discussioncontrasting
confidence: 90%
“…Lab composite onlays did not show any significant improvement in the fracture resistance of prepared teeth when compared to lab composite inlays as prepared cusps have less tooth structure, thus could not withstand heavy compressive load . Conversely, this finding did not show any agreement with another previous study which revealed that lab composite onlays (with or without fiber reinforcement) increased the fatigue resistance of restored teeth rather than lab composite inlays as cuspal coverage with lab composite promotes extracoronal strengthening and protects against further crack propagation and fracture tendency.…”
Section: Discussioncontrasting
confidence: 90%
“…Therefore, the authors decided to maintain the loading sequence and values but to modify the angle of force to 308 and to concentrate its application to the working cusp using a composite resin cylinder (Z100, 3M ESPE) as an antagonist. 24 This measure increases the stress to the restoration and simulates an extreme load configuration (nonworking contact).…”
Section: Discussionmentioning
confidence: 99%
“…The load application device type influenced in the fracture resistance values and in the failure mode of maxillary premolars restored with composite resin. The fracture resistance tests are largely used (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and are an important source of information, indicating which component is more fragile: the restoration, the dental structure or the adhesive interface. However, when performing mechanical tests, there is a number of factors that could interfere on the resistance to fracture, such as the tooth embedding method (20), the crosshead Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used a universal testing machine to deliver a compressive load to the occlusal surfaces by means of various metallic devices such as steel sphere (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(14)(15)(16), steel cylinder (17,19), wedge shape device with a straight (18) and cast metal antagonist tooth (20,21). Some these devices contact only the restorative material (23), others contact the tooth structure, and others contact both the tooth structure and the restorative material. However, the correlation between the device used and the aim of each study is not clearly defined.…”
Section: Influence Of Different Load Application Devices On Fracture mentioning
confidence: 99%